1950 ve 1954 Genel Seçimlerinde Antalya - Sevilay ÖZER (Gazi Akademik Bakış)
With the transition to a multiparty political life, political life in Turkey has gained further momentum. With the establishment of the DP alongside the CHP, which has been in power for any years, the traditional election atmosphere has undergone a major change. The general elections which held in 1946 and then in 1950 were quite popular. In addition to the national press, the local press followed the elections with great interest. In this process, the parties engaged in an active propaganda activity and the public listened to the speeches of the candidates both at the rally squares and in the coffeehouses. Contrary to the 1946 elections, secret ballot and open counting were applied for the first time in the 1950 general election. In the 1950 elections, where the plurality voting system was implemented, DP was elected 7 deputies from Antalya and 8 in 1954 general elections. In this study, the determination of candidates for parliamentary election for DP and CHP in the general elections held in 1950 and 1954 in Antalya, the propaganda activities of the candidates, the issues they discussed during the election campaign and the results of the elections were evaluated in detail.